PERANAN KEPEMIMPINAN CAMAT DALAM MENUMBUHKAN KEDISIPLINAN PEGAWAI DI KANTOR KECAMATAN JEBRES KOTA SURAKARTA - Hasanah, Bastin Fitriatus; Santoso, Djoko; Subarno, Anton (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
Absract: The objectives of this research are to investigate: (1) how Chief of Jebres Sub-district Office, Surakarta city plays his leadership role in growing the discipline behavior of its employees; (2) what constraints are encountered by Chief of Jebres Sub-district Office, Surakarta city in internalizing the discipline of its employees; and (3) what solutions are taken by Chief of Jebres Sub-district Office to deal with the prevailing constraints to the materialization of the discipline behavior of its employees. This research used the qualitative embedded single case study method. The results of the research are as follows: 1) Chief of Jebres Sub-district Office, Surakarta city plays his leadership role through the discipline behavior internalizations such as: (a) giving exemplification through discipline attitude; (b) giving motivation to the employees; (c) attempting to fulfill their needs and prosperity; and (d) implementing the discipline upholding consistently. 2) The constraints occurring in nurturing the discipline of the employees of Jebres Sub-district Office are as follows: (a) internal constraints: some employees bear the characters and personalities which are apathetic to advices, and some are lack of responsibilities in executing their duties and work and (b) external constraints: the external constraints occurring in internalizing the discipline of the employees of Jebres Sub-district Office are mainly related to the work environment. 3) The prevailing constraints occurring in internalizing the discipline of the employees are as follows: (a) upholding the prevailing laws and regulations and nurturing the employees; and (b) maintaining the communication and good relations among the employees.